Advances in drug research. - Testa, Bernard; Meyer, Urs A., 1938- (Academic Press, 1996)
This volume continues the trend for Advances in Drug Research of shorter, but more frequent volumes. In line with the tradition of the series, chapters on general themes are interspersed with chapters on specific drug classes and targets.